2012
DOI: 10.1007/s10048-011-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanistic characterization of two exonic L1CAM variants located in trans in an obligate carrier of X-linked hydrocephalus

Abstract: Mutations in the gene encoding the neural cell adhesion molecule L1CAM cause several neurological disorders collectively referred to as L1 syndrome. We report here a family case of X-linked hydrocephalus in which an obligate female carrier has two exonic L1CAM missense mutations in trans substituting amino acids in the first (p.W635C) or second (p.V768I) fibronectin-type III domains. We performed various biochemical and cell biological in vitro assays to evaluate the pathogenicity of these variants. Mutant L1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…We also used ConSurf server; the nsSNPs that are located at highly conserved amino acid positions tend to be more deleterious than nsSNPs that are located at non-conserved sites. (supplemental figure 4 for ConSurf result, which is available at https://www.biorxiv.org/ ) There were some studies that have been reported which show pathogenic nsSNPs that cause L1 syndrome (11,(70)(71)(72)(73)(74)(75)(76)(77)(78), which is corresponding with our results. It has been observed that L1CAM polymorphisms are associated in several types of human cancers 79).…”
Section: Discussionsupporting
confidence: 90%
“…We also used ConSurf server; the nsSNPs that are located at highly conserved amino acid positions tend to be more deleterious than nsSNPs that are located at non-conserved sites. (supplemental figure 4 for ConSurf result, which is available at https://www.biorxiv.org/ ) There were some studies that have been reported which show pathogenic nsSNPs that cause L1 syndrome (11,(70)(71)(72)(73)(74)(75)(76)(77)(78), which is corresponding with our results. It has been observed that L1CAM polymorphisms are associated in several types of human cancers 79).…”
Section: Discussionsupporting
confidence: 90%
“…Co-expression of pEGFP was observed in at least 80–90% of NEGR1-positive cells in all experiments and conditions (data not shown). Cell aggregation assay was essentially performed as described [53] and quantified by determining the increase of average areas of green fluorescent cells and aggregates between 0 min (t1) and 60 min (t2) in each condition using Image J software. The calculated t2/t1 ratios were expressed relative to control cells expressing pEGFP alone.…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture, immunocytochemistry, and immunoblotting NSC-34 cells were cultured and transfected using polyethylenimine (Marx et al 2012). hemagglutinin (HA)-tagged HIF-1a expression constructs (pcDNA3-HIF-1a-827 and pcDNA3-HIF-1a-736), and the hypoxia response elements (HRE) firefly luciferase reporter plasmid were previously described (Gothi e et al 2000;Arsham et al 2002).…”
Section: Gene Expression Analysismentioning
confidence: 99%